2018
DOI: 10.1016/j.yebeh.2018.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug treatment of generalized tonic–clonic seizures: An evaluation of regulatory data and five criteria for drug selection

Abstract: Ultimately, the choice of AED depends on all these factors but particularly on efficacy and adverse effects. Different patients will weigh the various factors differently, and the role of the treating physician is to provide accurate information to allow patients to make informed choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 87 publications
(111 reference statements)
1
13
0
2
Order By: Relevance
“…FBTCS are an adverse prognostic factor for seizure freedom after temporal lobe resection 6–8 . It remains unclear why temporal lobe seizures generalize in some patients but not in others 9,10 . It is crucial to identify factors that make some patients susceptible to FBTCS despite taking seizure‐suppressing medications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBTCS are an adverse prognostic factor for seizure freedom after temporal lobe resection 6–8 . It remains unclear why temporal lobe seizures generalize in some patients but not in others 9,10 . It is crucial to identify factors that make some patients susceptible to FBTCS despite taking seizure‐suppressing medications.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that impairments in specific brain regions support FBTCS, after finding disrupted structure and function in circuits mediated by thalamus and basal ganglia 6,12–18 . It has also been suggested that FBTCS have a different mechanism to primary generalized seizures, with more complex patient‐specific spread 10,19–23 . There is a need to investigate the full complexity of brain networks, 24 beyond the canonical thalamocortical pathways, 12 to delineate networks underlying FBTCS.…”
Section: Introductionmentioning
confidence: 99%
“…Lamotrigine is a novel antiepileptic drug of the phenyltriazine class which is used widely in epilepsy, simple and complex seizures, generalized tonic-clonic seizures, and bipolar disorder. 1,2 Its chemical name is 3, 5-diamino-6-(2,3-dichlorophenyl)-1,2,4-triazine. 3 It acts by regeneration and modification of neurons function and Schwann cells by reducing glutamate release from nerve terminals in addition to a protective effect against cytotoxicity resulting from inhibition of mitochondrial respiratory complex I.…”
Section: Introductionmentioning
confidence: 99%
“…For generalized-onset tonic-clonic seizures, valproate is recommended as first choice (except in women/girls of childbearing potential); lamotrigine and topiramate are valuable alternatives, however, lamotrigine can aggravate myoclonic seizures (e.g., in patients with Juvenile Myoclonic Epilepsy [JME]) ( Table 2) [21-23, 27, 31, 32]. Levetiracetam is effective as monotherapy for generalizedonset tonic-clonic seizures [27,31,32] but is currently not reimbursed for this seizure type in Belgium. Carbamazepine can also be considered as monotherapy for generalized-onset tonic-clonic seizures but is not effective against Information retrieved from each AED's summary of product characteristics (SmPC) and [25] b…”
Section: Generalized-onset Seizuresmentioning
confidence: 99%